Faktor-Faktor yang Mempengaruhi Kemiskinan dan Pengangguran di Kota Jambi - Harlik Harlik; Amri Amir; Hardiani Hardiani (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2013)
The purpose of this study was : (1) To analyze the factors that affect poverty in the City of Jambi during the period 2000-2011, (2) To analyze the factors causing high unemployment in the city of Jambi during the period 2000-2011, and (3) To analyze the relationship between poverty and unemployment in the city of Jambi during the period 2000-2011. The data used in this study is secondary data from the years 2000-2011. BPS data sources derived from the city of Jambi and Diskakertrans city of Jambi. Analysis tools used in this research is a method of multiple linear regression and correlation. The results showed that: (1). Simultaneously (together) variable population density, education level and the unemployment rate, and a significant positive effect on the level of poverty in the city of Jambi. While partially independent variables that significantly influence the level of education level and the level of poverty is unemployment. Variables influence population density, education level and the unemployment rate is equal to the poverty rate of 92,40 percent, (2). Simultaneously (together) variable education level and health level have positive and significant effect on the unemployment rate in the city of Jambi. While partially independent variables had significant effect on the unemployment rate in the City of Jambi is education level. Variables influence education level and health level rate is equal to the unemployment rate of 42,6 percent; (3). Levels of poverty and unemployment rate in the city of Jambi has a negative correlation with a correlation coefficient of -0.290. Keywords: Population Density, Unemployment Rate, Education Level